PSIKOEDUKASI REGULASI EMOSI GUNA MENANGGULANGI KECEMASAN SISWA AKIBAT MEDIA SOSIAL DI SEKOLAH INDONESIA DAVAO FILIPINA - Siti Jaro'ah; Farida Istianah; Citra Fitri Kholidya; Nur Ika Sari Rakhmawati; Wiryo Nuryono (Yayasan Education and Social Center, 2023)
It was found that anxiety is correlated with problematic social media use and is widely experienced by individuals, thus posing a threat to adolescents. This issue needs to be addressed, one of which is by providing emotion regulation psychoeducation. It aims to equip students with adaptive socio-psychological skills in the technological and digital era. Psychoeducation was provided to students of Indonesian Davao School Philippines online. The materials provided were related to social media, anxiety, and emotion regulation. Prior to and after the implementation, students were given questionnaires to determine the increase in understanding and knowledge. The results showed that the psychoeducation provided further improved students' understanding of social media and emotion regulation. The implications of this service can contribute to students' ability to use social media wisely in the digital and technological era.